Pengaruh Kualitas Sumber Daya Manusia, Komitmen Dan Motivasi Kerja Terhadap Kinerja Pegawai Inspektorat Kabupaten Banyuasin - R.A. Rodia Fitri Indriani (Program Magister Manajemen Indo Global Mandiri University, 2021)
This study aims to determine whether the variable Human Resouces Quality (X1), Commitment (X2) and Work Motivation (X3) a significant influence on Employee Performance (Y) Inspektorat Kabupaten Banyuasin. Implementation of this study for 6 (six) months including the design, conduct and reporting of research results. This case study aims to determine the effect of Human Resouces Quality, Commitment and Work Motivation on Employee Performance Inspektorat Kabupaten Banyuasin either partially or jointly. In population research in question is the entire employee Inspektorat Kabupaten Banyuasin with a sample size of 41 peopl. The results were obtained regression coefficient Human Resouces Quality (X1) of 0.426, Commitment (X2) of 0.128 and Work Motivation (X3) of 0.626 and also produces a constant value of 12.260. So that the multiple linear regression equation is as follows :Y = 12.260 + 0.426X1 + 0.128X2 + 0.626X3 + e. While the results of correlation 0,712, which means having a strong relationship between the independent variables and the dependent variable, also obtained by the coefficient of determination (R square) of 0.506. This value can be interpreted to mean that the percentage of influence Human Resouces Quality, Commitment and Work Motivation on Employee Performance was 50,6% while the remaining 49,4% is influenced by other variables not included in this study. Implementation is that the Inspektorat Kabupaten Banyuasin continuously improve Human Resouces Quality, Commitment and Work Motivation, so that the consciousness of themselves together to always strive to achieve the goals that have been set (Employee Performance Inspektorat Kabupaten Banyuasin).